Awareness and knowledge of the Good Samaritan Drug Overdose Act among people at risk of witnessing an overdose in British Columbia, Canada: a multi-methods cross sectional study - Emma Ackermann; Bradley Kievit; Jessica Xavier; Skye Barbic; Max Ferguson; Alissa Greer; Jackson Loyal; Zahra Mamdani; Heather Palis; Bernie Pauly; Amanda Slaunwhite; Jane A. Buxton (BMC, 2022)
Abstract Introduction Bystanders to drug overdoses often avoid or delay calling 9-1-1 and cite fear of police involvement as a main reason. In 2017, the Good Samaritan Drug Overdose Act (GSDOA) was enacted by the Canadian government to provide people present at an overdose with legal protection from charges for simple drug possession, and conditions stemming from simple possession. Few studies have taken a multi-methods approach to evaluating the GSDOA. We used quantitative surveys and qualitative interviews to explore awareness, understanding, and perceptions of the GSDOA in people at risk of witnessing an overdose. Methods Quantitative cross-sectional surveys and qualitative telephone interviews were conducted with adults and youth at risk of witnessing an overdose across British Columbia. Cross-sectional survey participants were recruited at 19 Take Home Naloxone sites and online through Foundry. Multivariable logistic regression models were constructed hierarchically to determine factors associated with GSDOA awareness. Telephone interview participants were recruited by research assistants with lived/living experience of substance use. Deductive and inductive thematic analyses were conducted to identify major themes. Results Overall, 52.7% (n = 296) of the quantitative study sample (N = 453) reported being aware of the GSDOA. In multivariable analysis, cellphone possession (adjusted odds ratio [AOR] = 2.19; 95% confidence interval [CI] 1.36, 3.54) and having recently witnessed an opioid overdose (AOR = 2.34; 95% CI 1.45, 3.80) were positively associated with GSDOA awareness. Young adults (25 - 34 years) were more likely to be aware of the Act (AOR = 2.10; 95% CI 1.11, 3.98) compared to youth (16-24 years). Qualitative interviews (N = 42) revealed that many overestimated the protections offered by the GSDOA. To increase awareness and knowledge of the Act among youth, participants recommended adding the GSDOA to school curricula and using social media. Word of mouth was suggested to reach adults. Conclusion Both awareness and knowledge of the GSDOA remain low in BC, with many overestimating the protections the Act offers. Dissemination efforts should be led by people with lived/living experience and should target those with limited awareness and understanding of the Act as misunderstandings can erode trust in law enforcement and harm reduction policy.